Comparative Study of UPV and IE Results on Concrete Cores from Existing Structures - Siorikis, Vassilis G.; Antonopoulos, Constantinos P.; Hatzigeorgiou, George D.; Pelekis, Panagiotis (Salehan Institute of Higher Education, 2024)
Dynamic non-destructive methods (NDT) are particularly attractive owing to their time and cost efficiency when compared to conventional uniaxial compressive strength tests. However, the results of these methods are highly scattered; therefore, they are primarily used for qualitative material characterization. One of the most important NDT results is the calculation of the dynamic Young’s modulus, which is associated to the uniaxial compressive strength (UCS) of concrete. The ultrasonic pulse velocity (UPV) is the most commonly used NDT. The limitation of this method is that it directly depends on knowledge of the Poisson’s ratio, and an assumption of its value must be made. This assumption results in highly scattered results. In contrast, the impact echo method (IE) can result in a dynamic Young’s modulus calculation without knowing the Poisson’s ratio. The limitation of this method is that it is dependent on the specimen’s slenderness, which in turn depends on the Poisson’s ratio. This study investigates the IE method’s applicability to short cylinders. A comparison of the UPV and IE methods is made, and the error in the dynamic Young’s modulus value derived by assuming Poisson’s ratio value in the UPV method is calculated. The authors conducted a numerical analysis and recently proposed the use of a shape correction factor (SCF) to apply the IE results for short cylinders, considering the influence of the slenderness (L/D) of the samples. For the first time worldwide, an extensive experimental study on 232 concrete samples with L/D ≈ 1.0 confirmed the wide spread of UPV test results and showed that it can lead to an error on Young’s Modulus determination by up to 50% owing to the adoption of an arbitrary Poisson’s ratio value. In contrast, using the SCF yields IE results with a ±2% error. A new methodology, ultrasonic pulse impact echo synergy (UPIES), is proposed by performing both UPV and IE tests on the specimens and using the SCF. The Poisson’s ratio and, consequently, the Young’s modulus can be accurately determined. Doi: 10.28991/CEJ-2024-010-09-03 Full Text: PDF